Tuberculosis and human immunodeficiency virus co-infected patients’ mortality rate and its predictors in Dire Dawa, Eastern Ethiopia, 2018 - Habtegiorgis, Samuel Derbie; Amante, Tariku Dingeta; Petrucka, Pammla (International Journal of Scientific Reports, 2023)
Background: Tuberculosis and human immunodeficiency virus (TB/HIV) co-infection is an important global public health problem and result multidirectional tricky. The mortality rate of co-infected patient’s comes from many aspects or factors. Identification of these factors is important for planning and for the intervention of care and treatment. The aim of this study was to examine the co-infected patients’ mortality rate and its predictors. Methods: A five-year retrospective cohort study was employed among 471 randomly selected TB/HIV co-infected patients enrolled from January, 2012 to December, 2016. Relevant variables of data were collected from patients ‘medical cards. The collected data were entered into Epi-data 4.2.0.0 and exported to SPSS version 24 for analysis. Univariate analyses were used to describe the baseline characteristics of the patients. Kaplan Meir curve were used for the comparison of time to recovery among the different groups of patients and Cox model was used to identify independent predictors. Results: A total of 79 (16.8%) deaths occurred during the median follow-up period of 685 days. being infected with pulmonary tuberculosis (PTB) [AHR=1.99 (95% CI:1.16-3.41)], WHO clinical stage III [AHR=2.88 (95% CI:1.56-5.30)], IV [AHR=4.20 (95% CI:2.21-8.01)], ambulatory functional status [AHR=4.15 (95% CI:1.57-10.98)], bedridden functional status [AHR=6.34 (95% CI:2.43-16.59)] and delayed Co-trimoxazole preventive therapy [AHR=2.45 (95% CI:1.54-3.91)] were important predictors associated with high mortality rate of TB/HIV co-infected patients. Conclusions: about one to six TB/HIV co-infected persons died in their course of treatment follow-up. Important contributing factors were PTB infection, WHO clinical staging III and IV, ambulatory and bed ridden functional status and delayed co-trimoxazole preventive therapy.